The results of polymerase chain reaction and MALDI-TOF mass spectrometry versus phenotypic distinction between Klebsiella pneumoniae and Klebsiella oxytoca - Palusiak, Agata; Maciejewska, Anna; Łukasiewicz, Jolanta (Frontiers in Microbiology, 2025)
IntroductionKlebsiella pneumoniae and K. oxytoca are members of Enterobacteriaceae. They are Gram-negative, non-motile rods that are ubiquitous in the environment and part of the human intestinal microbiota. These opportunistic pathogens may cause pneumonia and urinary tract infections. Klebsiella species are genetically and biochemically similar; therefore, it is important to find reliable methods for their differentiation.MethodsThis study presents the results of biochemical assays, PCR, and MALDI-TOF mass spectrometry (MS) performed on 35 Klebsiella isolates obtained from the urine of patients from central Poland.ResultsAmong biochemical methods, the indole test demonstrated the highest discriminatory power, whereas the determination of growth at 10°C was the least effective. For all strains biochemically identified as K. pneumoniae, a 108-bp amplicon was detected, indicating the presence of the rpoB gene in their genome. Only 12 K. oxytoca isolates produced a product of the pehX gene. All tested strains were analyzed using the MALDI-TOF Biotyper, which confirmed, with high-quality scores, their identification based on api 20E and indole tests. Strain 0.011 was identified as Raoultella ornithinolytica.ConclusionMALDI-TOF MS analysis proved to be the most reliable method for identifying K. oxytoca and K. pneumoniae, with the potential for phylogroup differentiation.